Regional and global patterns of internationalisation of Finnish MNES - Sarianna M. Lundan; Juha Tolvanen (The Research Institute of the Finnish Economy (ETLA), 2008)
Much of the recent evidence on the internationalisation patterns of Finnish MNEs has come from analyses of the Top 30 firms. This paper uses newly available data from the Orbis database on the foreign affiliates of Finnish MNEs, and compares this to the existing sources of data from the Bank of Finland and Statistics Finland. By utilising firmlevel that includes smaller internationalising firms, we are able to get a more comprehensive picture of the international activities Finnish firms. We are also able to present an analytically grounded classification of the different types of internationalising firms in terms of the spread or entropy of their international activities. Such a classification will enable a more fine-grained measure of internationalisation in future studies that examine for example the effects of internationalisation on the home country.
Keywords: D21; D24; F21; F23; M16; 330; Multinational enterprises; internationalisation; entropy; Globalisierung; Multinationales Unternehmen; Auslandsniederlassung; Finnland